2021
DOI: 10.3238/arztebl.m2021.0163
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Evaluation of the Population-Based Integrated Health Care System “Gesundes Kinzigtal”

Abstract: ealth care in Germany is provided-historically grown-in sectors that are largely distinct from one another, at the interfaces of which recurrent losses of information and "breaks in care" occur, leading to negative effects on the quality and cost of care (1, 2). One approach to improving the effectiveness and efficiency of health care is seen in "integrated care" with horizontal and vertical networks of actors. A concept of this kind was developed for a rural area by Optimedis AG and the "Kinzigtal Medical Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
5
1
1
Order By: Relevance
“…Previous studies that have evaluated the performance of QuATRo networks in Germany using claims data have focused on single networks. As in the present study, these have yielded mixed results, showing either no significant differences in healthcare quality 34 or better healthcare in the network compared to regular care, albeit with a limited set of indicators related to DMPs. 8 In the UK, where PNs exist mostly as networks of GPs in the English NHS, the previous literature is limited and provides insufficient evidence to draw firm conclusions about the effects of networks on quality of care.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies that have evaluated the performance of QuATRo networks in Germany using claims data have focused on single networks. As in the present study, these have yielded mixed results, showing either no significant differences in healthcare quality 34 or better healthcare in the network compared to regular care, albeit with a limited set of indicators related to DMPs. 8 In the UK, where PNs exist mostly as networks of GPs in the English NHS, the previous literature is limited and provides insufficient evidence to draw firm conclusions about the effects of networks on quality of care.…”
Section: Discussioncontrasting
confidence: 60%
“…The integration of medical and nursing care refers to the process in which physicians and nurses work together to provide medical care to patients through communication and coordination between medical and nursing care under the premise of equal autonomy and with certain expertise and competence (8,9). FTS focuses on a multidisciplinary approach to problem solving and decision making through the implementation of an integrated medical and nursing approach, which brings together the strengths of each field and integrates them with a common goal, so that an integrated medical and nursing approach to rapid perioperative rehabilitation interventions is necessary to enable patients to recover after surgery (10,11). Domestic and international studies (12,13) have reported that integrated medical and nursing rehabilitation interventions based on the FTS concept have been used in thoracic surgery, spine surgery, orthopedics, and cancer patients with more extensive results making them safe, effective, and improving their prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Luohu model, the integrated care model developed in other countries and regions also found positive changes in patients' knowledge, attitude, and behaviour. "Healthy kinzigtal" was an integrated care model launched in Germany in 2004 [30]. After 9 years of operation of this model, 24% of patients lived healthier than before [31].…”
Section: Discussionmentioning
confidence: 99%